Health Care Routing Problem: A Systematic Literature Review - Wijayanti, Erny Rahayu; Normasari, Nur Mayke Eka; Purnama, Siti Aghnia Salsabilla; Faisa, Kurniawan Nur (Institut Teknologi Dirgantara Adisutjipto, 2023)
Routing issues have recently gained the attention of many researchers due to the various advantages they provide. Minimizing costs, travel time, and the number of workers will help company resolve the issue. This paper contains a review of 53 papers characterized by their objectives, function, and method of completion. There are two types of objective functions: single-objective functions and multiple-objective functions. Exact method, hybridization and simulation methods, heuristic, and metaheuristic are the solution methods used. Further research is supposed to generate advanced metaheuristic algorithms that have already been revealed to be useful for both single and multi-objective problems in this field. A more in-depth investigation of the performance of metaheuristic algorithms is required in future research.